Strategic Management of Boarding Schools for Enhanced Learning Quality - Geh, Nyak; Bahrun, Bahrun; Niswanto, Niswanto (Heca Sentra Analitika, 2024)
This study examines the management of boarding school programs at junior high schools in South West Aceh Regency, Indonesia, and their impact on educational quality. Using qualitative methods, it investigates the planning, implementation, and evaluation of these programs at two schools: Boarding School Ibnu Sina and Boarding School Jabal Nur Jadid. The findings show: (1) The planning adheres to government regulations and involves the school community; (2) Implementation follows structured daily routines integrating academic and religious activities; (3) Regular evaluations reveal improvements in student discipline and academic performance. The boarding school environment is found to enhance educational quality and foster students' moral development. The study highlights the importance of comprehensive planning, stakeholder involvement, structured implementation, and continuous evaluation in the success of boarding school programs.